PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP UNIT GEDUNG A-RSCM JAKARTA - Indra Jaya; Indra Syarufudin (Universitas Pakuan, 2015)
The hospital is an institution in the field of health care, but this time a lot of changes. At the beginning ofits development, the hospital is an institution that serves the social, but with the private hospitals, makingthe hospital more refers as an industry engaged in the field of health care by management based on themanagement of a business entity. The results obtained from this study is the general level of satisfactionin RSUPN Dr. Cipto Mangunkusumo good enough. The author explains through the level of concordancebetween performance and expectations according to respondents' perception of 100.03%. As for therelationship Chi-Square analysis concluded that the quality of service RSUPN DDR. CiptoMangunkusumo especially inpatient class 2 in unit A building, give significant influence on satisfactionfor the customer/patient , both at the level of performance and the level of expectation. At the level ofperformance, obtained statistical Chi-Square at 383.938 that was significant at 95% confidence level.While the level of expectation, obtained statistical Chi-Square at 312.468 that was significant at 95%confidence level.